2022
DOI: 10.1002/anie.202200692
|View full text |Cite
|
Sign up to set email alerts
|

Inside Back Cover: A Carbonic Anhydrase IX (CAIX)‐Anchored Rhenium(I) Photosensitizer Evokes Pyroptosis for Enhanced Anti‐Tumor Immunity (Angew. Chem. Int. Ed. 8/2022)

Abstract: Pyroptosis is a unique form of programmed cell death that is essentially proinflammatory and critical for immunity. In their Research Article(e202115800), Qian Cao, Zong‐Wan Mao, and co‐workers developed a carbonic anhydrase IX (CAIX)‐anchored photosensitizer, CA‐Re, that is capable of inducing and self‐reporting membrane rupture upon irradiation, as well as evoking pyroptosis to activate antitumor immunity. CA‐Re is the first metal‐complex‐based pyroptosis inducer, and this work provides a promising avenue fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 0 publications
0
40
0
Order By: Relevance
“…25 Recent membrane-anchoring PDT studies also revealed a pyroptosis pathway. 15,16 Hence, we explored whether our membrane-tethered activation design of aPYCI4 induced pyroptosis of APN-positive cancer cells. As anticipated, bubble-like protrusions around aPYCI4-treated HepG2 cells were observed upon irradiation with a 640 nm laser (Fig.…”
Section: Mechanistic Studies Of Membrane-tethered Activation Mediated...mentioning
confidence: 99%
See 2 more Smart Citations
“…25 Recent membrane-anchoring PDT studies also revealed a pyroptosis pathway. 15,16 Hence, we explored whether our membrane-tethered activation design of aPYCI4 induced pyroptosis of APN-positive cancer cells. As anticipated, bubble-like protrusions around aPYCI4-treated HepG2 cells were observed upon irradiation with a 640 nm laser (Fig.…”
Section: Mechanistic Studies Of Membrane-tethered Activation Mediated...mentioning
confidence: 99%
“…15 An alternative design is to utilize a membrane protein-targeting metal-complex PS that renders facile membrane anchoring. 16 However, these membrane anchoring designs rely on poly-cationic groups or poorly hydrophilic moieties, which may exhibit increased non-specific adsorption and toxicity with a concurrent high clearance rate. Besides, the short-wavelength excitation and non-activatable characteristics of these PSs can compromise their efficacy due to low penetration depth and collateral phototoxicity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Type II PDT relies on the energy transfer from excited PSs to triplet oxygen to generate singlet oxygen ( 1 O 2 ), while type I PDT is based on the electron transfer from PSs to surrounding oxygen or substrates to generate free radicals (superoxide anions, hydroxyl radicals, etc.). [2][3][4] Benefited from the localized light irradiation and the short action radius and lifetime of ROS, PDT holds the unique merits of precise spatiotemporal control, minimal invasiveness, high therapeutic specificity, and so forth. [5,6] To deliver PSs to tumor area, one of the most adapted strategies is to encapsulate PSs into waterdispersible nanoparticles, which not only Aggregation-induced emission (AIE) fluorogens provide new opportunities to promote efficient reactive oxygen species (ROS) production in aggregates, which represent the promising candidates to construct theranostic nanoparticles for photodynamic therapy (PDT), but the size effect has been rarely explored.…”
Section: Introductionmentioning
confidence: 99%
“…Photodynamic therapy (PDT), as a noninvasive method of cancer treatment, , has also acquired increasing consideration as it triggers robust pyroptosis and subsequent immune responses in a controllable manner through NIR laser irradiation. , Studies have shown that PDT-mediated pyroptosis can cause immunogenic tumor-cell death (ICD), in which dying cells release tumor-associated antigens (TAAs) and damage-related molecular patterns (DAMPs), such as HMGB-1, adenosine triphosphate (ATP), and calcitonin (CRT), thus increasing the immunogenicity of the tumor microenvironment. The photosensitizer chlorin e6 (Ce6) has been shown to stimulate pyroptosis in multiple cancers, , but the poor water solubility and inadequate accumulation of Ce6 limit its further clinical application .…”
Section: Introductionmentioning
confidence: 99%